ANALYSIS ON THE PREDICTION OF BANKRUPTCY OF CIGARETTE COMPANIES LISTED IN THE INDONESIA STOCK EXCHANGE USING ALTMAN (Z-SCORE) MODEL AND ZMIJEWSKI (X-SCORE) MODEL - Prabowo, Satriya Candra Bondan (Universitas Brawijaya, Indonesia, 2019)
This study aims to identify the results of bankruptcy predictions using Altman (Z-Score) model and Zmijewski (X-Score) model. The object of this research is four cigarette companies listed in the Indonesia Stock Exchange from 2013 to 2017. This study finds that Altman (Z-Score) model and Zmijewski (X-Score) model produce similar results. Both models can be used as considerations in predicting bankruptcy. The results of the Altman model show that PT. Sampoerna Tbk had not been in bankruptcy potential during the study period, PT. Gudang Garam Tbk was in the vulnerable zone from 2013 to 2015, PT. Wismilak Tbk was not in bankruptcy potential in 2013, in the vulnerable zone from 2014 to 2015, and not in bankruptcy potential from 2016 to 2017, and PT. Bentoel Tbk was in bankruptcy potential from 2013 to 2015 and the vulnerable zone from 2016 to 2017. The results of the Zmijewski Model show that three companies did not have the potential for bankruptcy; they are PT. Gudang Garam Tbk., PT. Sampoerna Tbk., and PT. Wismilak Tbk. However, PT. Bentoel Tbk. Had the potential for bankruptcy in from 2013 to 2015 and had no potential bankruptcy from 2016 to 2017.